Characterization of polychlorinated biphenyl congeners in surface sediments of the Changjiang Estuary and adjacent shelf by high-resolution sampling and high-resolution mass spectrometry. Issue 1 (15th November 2017) - Liu, Aifeng; Wang, Yawei; Xian, Mo; Zhao, Zongshan; Zhao, Bin; Wang, Jinpeng; Yao, Peng
Abstract: Due to limited samples and low-resolution analysis, conflicting findings on major polychlorinated biphenyl (PCB) congeners and their origins remain in the East China Sea (ECS). Based on high-resolution sampling and high-resolution mass spectrometry analysis, 72 surface sediment samples from the Changjiang Estuary and adjacent ECS shelf were determined to characterize 39 PCB congeners. PCBs (∑39 PCBs) ranged from 0.003 to 16.18 ng/g dw, presenting a decreasing seaward trend. Tri-, tetra- and penta-CBs were the main components, accounting for > 64% of ∑39 PCBs in most samples. Tetra-CBs were the dominant congeners, corresponding to results of sediments from Changjiang middle reach and soils from Changjiang Delta. Comparison between PCBs and sediment properties indicated there may be a deposition boundary of 30°N. In the north, the spatial distribution of PCBs is controlled by Changjiang input and hydrodynamic conditions, while in the south closely related to combination of local source and riverine input. Highlights: PCB deposition characteristics were studied in ECS and adjacent shelf. We analyzed 39 PCB congeners by high-resolution sampling and high-resolution MS. Low chlorinated PCBs were main components and tetra-CBs were dominant congeners. A boundary of 30°N was found based on PCB deposition characteristics and sources.